2007
DOI: 10.1038/nn1958
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFI regulates the balance of cortical patterning between frontal/motor and sensory areas

Abstract: We used cortex-specific deletion of the transcription factor gene COUP-TFI (also known as Nr2f1) in mice to demonstrate previously unknown fundamental roles for it in patterning mammalian neocortex into areas. The highest COUP-TFI expression is observed in the cortical progenitors and progeny in parietal and occipital cortex that form sensory areas, and the lowest expression was observed in frontal cortex that includes motor areas. Cortical deletion of COUP-TFI resulted in massive expansion of frontal areas, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
313
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(336 citation statements)
references
References 33 publications
21
313
2
Order By: Relevance
“…Confirming this hypothesis, we found that even before grafting most ESC-derived neural progenitors expressed the CoupTFI (NR2F1) and CoupTFII (NR2F2) transcription factors (81.64 6 2.22% and 95.1 6 1.23%, respectively, Supplementary Fig. 8f, g), which are preferentially expressed in the embryonic occipital/visual cortex 34,35 .…”
Section: Cortical Axonal Projections Of Esc Neuronssupporting
confidence: 73%
“…Confirming this hypothesis, we found that even before grafting most ESC-derived neural progenitors expressed the CoupTFI (NR2F1) and CoupTFII (NR2F2) transcription factors (81.64 6 2.22% and 95.1 6 1.23%, respectively, Supplementary Fig. 8f, g), which are preferentially expressed in the embryonic occipital/visual cortex 34,35 .…”
Section: Cortical Axonal Projections Of Esc Neuronssupporting
confidence: 73%
“…Our retrograde tracings from the spinal cord demonstrate that the tract originates largely from the corticothalamic neurons in layer mVI within the abnormally expanded motorized cortex (17). Thus, these misspecifed neurons may not be integrated into appropriate cortical motor neuronal networks, and therefore are unable to contribute to fine motor control.…”
mentioning
confidence: 89%
“…We next investigated how the increase in motor area size (17), and the reassignment of the corticospinal connectivity to layer VI corticothalamic neurons, might affect sensorimotor function in COUP-TFI adult mutant mice. We first investigated sensorimotor function by using an adhesive patch removal task (25), in which the mouse has to remove a piece of adhesive patch placed on each hindpaw.…”
Section: Coup-tfi Controls the Area-specific Timing Of Csmn Specificamentioning
confidence: 99%
See 2 more Smart Citations